PENERAPAN METODE AHP UNTUK PEMILIHAN TOKO ONLINE TAS WANITA PADA PLATFORM SHOPEE - Herlina Trisnawati; Veranita Veranita; Sakius Tarigan (Jurnal Sistem Informasi dan Informatika (Simika), 2022)
Abstract: Today shopping online for daily needs has become a culture for some of our society, especially with the Covid-19 pandemic condition that has been going on for a long time, making us to do more activities at home. This has increased the interest in online shopping, especially for women who like to shop, making online stores an alternative to still being able to shop. With conditions like this, many new online shops or online stores that come from these non-online stores have joined in an e-commerce platform. As online stores increase, the competition among online stores are getting tighter and a little bit confusing for consumers to determine which online store to shop for. We need a decision support system that can help assess and compare one store with another. Researchers will use the AHP (Analytic Hierarchy Process) method that works based on a hierarchical structure in determining criteria using the Multi-criteria Decision Making (MCDM) concept that utilizes the results obtained from eigenvectors through iterations to minimize differences in the assessments of a number of respondents. The results will prove that the decision support system for choosing a trustworthy online shop for women's bags is appropriate based on the dimensions of online store satisfaction. The results of this study will be obtained which online shop for women's bags that are selected or in demand for online shopping transactions. Keywords: Analytical hierarchy process (AHP), e-commerce, eigenvector, decision support system, online shop